In honor of Michael Grossman. (9th August 2018) - Markowitz, Sara; Kaestner, Robert
Abstract : This symposium is to celebrate the accomplishments of Michael Grossman on the occasion of his retirement from teaching. The articles selected are all written by Mike's former students and colleagues, and were presented in a session at the 2017 Annual Meeting of the Southern Economic Association. Each of the articles celebrate Mike's scholarly legacy in developing the field of health economics.